An impressive response with larotrectinib in a patient with a papillary thyroid carcinoma harboring an SQSTM1-NTRK1 fusion. Issue 4 (23rd February 2022) - Bargas, Sophie; Mc Leer, Anne; Mondet, Julie; Chabre, Olivier; Laramas, Mathieu
Abstract: NTRK rearrangements represent a very rare genomic abnormality among all cancers but can be detected in thyroid cancer with a non-negligible frequency of 2%. Dramatic clinical responses to therapies targeting NTRK chimeric proteins are now well described in the literature. SQSTM1-NTRK1 fusions have not yet been described in a full clinical case report. We report a patient with a papillary thyroid carcinoma harboring this unique rearrangement, with an impressive clinical and radiologic response to larotrectinib, a highly specific inhibitor.